Recent advances in employing plant rhizobacteria for environmental stress mitigation in plants - Xiu-Peng Song; Mei-Xin Yan; Qiang Liang; Xiao-Qiu Zhang; Chang-Ning Li; Mukesh Kumar Malviya; Anjney Sharma; Qaisar Khan; Dao-Jun Guo; Yu-Xiang Li; Krishan K. Verma; Yang-Rui Li (Plant Stress)
Plants face a variety of abiotic stresses that can severely impact agricultural productivity and crop quality. Traditional methods, such as use of chemical inputs and resistant crop varieties, have had limited success, especially when suffering from multiple environmental stresses. Rhizobacteria with growth-promoting properties exhibit considerable diversity and inhabit the root zone of plants, thereby imparting multifaceted advantages to their host organisms. These bacteria can directly enhance plant performance by aiding in nutritional uptake, regulating phytohormones and mitigating the adverse impacts of stresses. Plant-associated rhizobacteria have been identified as a sustainable, eco-friendly biostimulant with potential to increase crop yield and abiotic stress tolerance capacity. Integrating these beneficial microbes into agricultural systems can reduce reliance on hazardous chemicals while improving the overall adaptability of agroecosystems to withstand adverse agroclimatic conditions. This review summarizes the recent advancements in understanding how beneficial microbes enhance plant stress tolerance, including direct nutritional support, phytohormone regulation, and induced systemic defences. PGPR-based biotechnologies employing bioinoculants provide better solutions for sustainable agriculture, reducing reliance on anthropogenic agrochemicals. This paper also aims to highlight the potential use of eco-friendly bioinoculants enhancing agricultural yield, ensuring sustenance food security and safety in the era of climate change.